2022
DOI: 10.1111/febs.16390
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies gone bad – the molecular mechanism of light chain amyloidosis

Abstract: Light chain amyloidosis (AL) is a systemic disease in which abnormally proliferating plasma cells secrete large amounts of mutated antibody light chains (LCs) that eventually form fibrils. The fibrils are deposited in various organs, most often in the heart and kidney, and impair their function. The prognosis for patients diagnosed with AL is generally poor. The disease is set apart from other amyloidoses by the huge number of patient‐specific mutations in the disease‐causing and fibril‐forming protein. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 231 publications
(296 reference statements)
0
36
0
Order By: Relevance
“…Survival of patients with systemic amyloidosis is extremely heterogeneous depending on the organs involved and the presence and extent of cardiac damage. Patients with localized amyloidosis have a considerably better prognosis than do those with systemic disease [5]. Hence, the early diagnosis of the amyloid process would provide the highest degree of therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Survival of patients with systemic amyloidosis is extremely heterogeneous depending on the organs involved and the presence and extent of cardiac damage. Patients with localized amyloidosis have a considerably better prognosis than do those with systemic disease [5]. Hence, the early diagnosis of the amyloid process would provide the highest degree of therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…[2,[4][5][6][7][8][9][10] It is often observed that such fluid-like droplet phases undergo liquid-to-solid gel-like phase transitions over time, which upon maturation (or expedited by disease-associated mutations) lead to fibril formation and the development of pathological diseases, such as Parkinson's, Alzheimer's, cataract, and antibody light-chain (AL) amyloidosis. [11,12] In AL amyloidosis, fibrils are deposited in various organs, most often in the heart and kidney, and impair their function. [12] LLPS is generally driven by weak multivalent interactions, such as electrostatic, hydrophobic, π-π and cation-π interactions, [13,14] and strongly affected by external conditions including temperature, pH, ionic strength, and the types and concentrations of excipients.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] In AL amyloidosis, fibrils are deposited in various organs, most often in the heart and kidney, and impair their function. [12] LLPS is generally driven by weak multivalent interactions, such as electrostatic, hydrophobic, π-π and cation-π interactions, [13,14] and strongly affected by external conditions including temperature, pH, ionic strength, and the types and concentrations of excipients. Recently, we and others observed that protein systems undergoing LLPS can be very sensitive to pressure, [15][16][17][18][19][20][21][22] thus suggesting that pressure modulation may be used to suppress LLPS formation and subsequent irreversible aggregation and fibrilization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these patient variants, only a limited number has been analyzed on the protein level. These analyses have revealed the presence of "active", fibrilpromoting mutations, and "silent" ones which do not induce the fibril pathway 8 . One of the well-characterized AL variants is FOR005, which was derived from a patient with cardiac involvement.…”
mentioning
confidence: 99%